Evaluation and application of molecular genotyping on nosocomial pathogen-methicillin-resistant Staphylococcus aureus isolates in Guangzhou representative of Southern China. (June 2017) - Miao, Jian; Chen, Lequn; Wang, Jingwen; Wang, Wenxin; Chen, Dingqiang; Li, Lin; Li, Bing; Deng, Yang; Xu, Zhenbo
Abstract: Staphylococcus aureus is recognized as a typical food-born pathogen in food safety, and its rapid detection and typing methods are in desperate need. To study their evolution characteristics and drug resistance condition, Staphylococci isolates were subject to the investigation. Strain identification were subjected to standard procedures (colony morphology, Gram staining, Vitek 2 automated system and the API commercial kit), and fingerprinting was then performed with RAPD-PCR amplification. In this study, 179 isolated staphylococci were identified as MRSA. In addition, Staphylococci isolates were subjected to three different fingerprinting system (ERIC2, AP1 and AP7) and then genotyped based on significant diversities. Nosocomial epidemiology was then conducted according to the fingerprint result. To sum up, the RAPD method subjected for MRSA rapid genotyping have a broad application prospect in food safety and epidemiology. Highlights: MRSA rapid genotyping were applied in the study. RAPD method were subjected in this study. Epidemic condition was conducted based on RAPD.